Massacres and morality mass atrocities in an age of civilian immunity - Bellamy, Alex J., 1975- (Oxford : Oxford University Press, 2012)
Starting with the French Revolution, this text studies mass killing as perpetrated by states. In particular, it examines the role that civilian immunity has played in shaping the behaviour of perpetrators and how international society has responded.
Includes bibliographical references and index.
Description based on print version record.
Keywords: War crimes -- History; Massacres -- History; Civilian war casualties -- History